Microstructure and mechanical properties of electrochemically cycled ice‐templated Li4Ti5O12 sintered anodes. (29th March 2022) - Parai, Rohan; Nie, Ziyang; Ghosh, Dipankar; Koenig, Gary M.
Summary: In the development of materials to meet increasing demands for energy storage, complex materials and systems will need to be investigated. One emerging area is multifunctional energy storage materials, where a battery electrode needs to satisfy other properties in addition to those associated with storing electrochemical energy. An example explored in this report is sintered electrodes for lithium‐ion batteries, where the electrode is only comprised of a porous sintered structure of the electroactive ceramic material. The sintered electrode must be multifunctional in that the porous ceramic itself must sustain the compressive mechanical stresses involved in fabricating the battery cell, as well as the stresses that result during electrochemical charge and discharge cycles. Toward meeting these multifunctional demands, anodes were fabricated using an ice‐templating technique, resulting in directionally porous materials. This study reports the microstructure and compressive mechanical properties of an ice‐templated sintered electrode material both before and after electrochemical cycling, revealing whether electrochemical cycling affects the microstructure and strength. For the specific electroactive material investigated as ice‐templated sintered anodes, the strain with electrochemical cycling was known to be minimal, and the microstructure and compressive strength were found to be retained after multiple charge and discharge cycles. These results suggest multifunctional ice‐templated lithium‐ion battery electrodes can be produced with both high strength and high cell level energy density. Novelty Statement: Ice‐templated sintered electrodes are multifunctional battery materials with desirable mechanical and electrochemical properties provided by their unique directionally aligned porous microstructure. This is the first study of these thick and high‐energy electrodes to report mechanical properties both before and after cycling. Microstructure and mechanical properties were retained after electrochemical cycling, suggesting that at least for relatively low strain materials that ice‐templated sintered electrodes are mechanically robust to strain induced by charge/discharge cycling. Abstract : This study evaluated the mechanical and microstructural properties of ice‐templated lithium‐ion battery electrodes containing only sintered electroactive material. Ice‐templating resulted in aligned pores that improve ion transport properties and aligned ceramic‐rich regions which increase electrode compressive strength. For the material evaluated herein, the mechanical strength and microstructure features were retained even after charge/discharge cycling of the material which involved substantial changes in intercalation/deintercalation of lithium from the solid material phase.